PELAKSANAAN PENGADAAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN PRODUKTIVITAS KERJA PADA SANGGAR KERAMIK NUR BANJARNEGARA - Haryanti, Titi (STMIK Amiko Purwokerto, 2008)
The grow of industry so fast, it because necessary of man that so much. Therefore, it can be oppurtunity to get potential human resources to increase sales volume and industry produktivity. Beside that, developing of human resorces is success key to increase producivity and to get the rihgt mans. If any mistakes, industry wil be ineffisiency because price and time from the human resources.Therefore,training of human resources it so important and include many aspects : education, healty, knowledge, acomodation, transportation, etc